2020
DOI: 10.1155/2020/8816522
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Predictors, and In-Hospital Mortality of Hepatic Encephalopathy in Patients with Liver Cirrhosis Admitted at St. Dominic Hospital in Akwatia, Ghana

Abstract: Background. Hepatic encephalopathy (HE) is one of the most debilitating complications of cirrhosis leading to death. Decrease in HE mortality and recurrence has been linked with timely identification and early treatment. There is a need to document the burden, predictors, and treatment outcomes of HE in an adult population with liver cirrhosis in our setting as only reports from resource-endowed countries abound in the literature. This study aimed therefore to determine the prevalence, predictors, and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
2
11
2
Order By: Relevance
“…Another important risk factor in patients with mortality from cirrhosis was alcohol accounting for 33.3% of cirrhosis deaths and 4.1% in those with HCC, and this finding is consistent with others assessing the same in Ghana [ 32 , 33 ]. The WHO estimated that in 2016, the attributable fraction of alcohol to liver cirrhosis was 39.6% and to liver cancer was 6% in males [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…Another important risk factor in patients with mortality from cirrhosis was alcohol accounting for 33.3% of cirrhosis deaths and 4.1% in those with HCC, and this finding is consistent with others assessing the same in Ghana [ 32 , 33 ]. The WHO estimated that in 2016, the attributable fraction of alcohol to liver cirrhosis was 39.6% and to liver cancer was 6% in males [ 34 ].…”
Section: Discussionsupporting
confidence: 89%
“…The study conducted by Bhanji et al revealed that the Child-Pugh class of patients with HE was higher than that of those without [ 16 ]. In a prospective study, Duah et al found that Child-Pugh score elevation was independently associated with the incidence of HE in hospitalized cirrhotic patients [ 17 ]. Taş et al investigated the predictive performances of noninvasive models in cirrhotic patients with HE who were admitted to ICU, followed by chronic liver failure-sequential organ failure assessment (CLIF-SOFA), APACHE II, and Child-Pugh score, which showed a better discriminative value of prognosis than MELD [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duah et al 18 concluded that raised serum creatinine and blood urea nitrogen levels were independent predictors of severe disease and overt hepatic encephalopathy in their patients. Our results were similar to their results in terms of serum creatinine levels.…”
Section: Discussionmentioning
confidence: 99%